2022
DOI: 10.18860/jetle.v3i2.15646
|View full text |Cite
|
Sign up to set email alerts
|

Using CLIL-Based English Materials Development for Business and Marketing in Vocational High School

Abstract: This paper aims to describe the use of Content and Language Integrated Learning (CLIL) approach in developing English language material for Business and Marketing major in vocational high school. It emphasizes on learning a subject and language all at once in language teaching. The study explores the needs of 21st century vocational students, CLIL advantages related to current curriculum, and its material resources. The results offer some relevant theories and considerations in developing the materials to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Based on content, CLIL's authentic materials are viewed as relevant by students, while the language, such as grammar or structure (that students have also learned in their GE materials), helps them finalize their ESP learning (Sulindra, 2019). In a more general scope, research has reported that CLIL suits the need of the Indonesian current curriculum (Rosyida & Effendy, 2022). It is obvious that CLIL offers aids both from the standpoint of language and subject-specific knowledge perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…Based on content, CLIL's authentic materials are viewed as relevant by students, while the language, such as grammar or structure (that students have also learned in their GE materials), helps them finalize their ESP learning (Sulindra, 2019). In a more general scope, research has reported that CLIL suits the need of the Indonesian current curriculum (Rosyida & Effendy, 2022). It is obvious that CLIL offers aids both from the standpoint of language and subject-specific knowledge perspectives.…”
Section: Introductionmentioning
confidence: 99%